Tinjauan Kriminologi Terhadap Pelaku Penipuan Jual Beli Album K-Pop - Sarah Azzahra; Sulistyanta Sulistyanta (Hakim, 2024)
The increase in K-Pop fans in Indonesia affects the high number of sales and purchases of K-Pop albums, which is an opportunity for irresponsible people to commit fraud. Provisions regarding online fraud are regulated in Article 378 of the Criminal Code and Article 28 paragraph (1) of the ITE Law. The purpose of this article is to examine criminology related to the factors that cause perpetrators to commit fraud in buying and selling K-Pop albums and efforts to overcome criminal acts of fraud on social media. Countermeasures related to fraud in buying and selling K-Pop albums are in the form of preventive efforts and repressive efforts. The research methodology used in this article is secondary data sources followed by primary data sources. Secondary data sources are obtained through literature studies, while primary data sources are obtained through interviews and observations.